Pengaruh Pengetahuan Keuangan, Sikap Keuangan Dan Perilaku Keuangan Terhadap Kinerja - Nuraeni Nuraeni; Ahmad Faisol Ghofiri; Khoirul Huda (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The purpose of this study was to analyze: (1) the effect of financial knowledge on MSME performance (2) the effect of financial attitudes on MSME performance (3) the effect of financial behavior on MSME performance (4) The effect of financial knowledge, financial attitudes and financial behavior on MSME performance. The type of research conducted by this researcher is a questionnaire research. The sampling technique was carried out using a non-probability sampling technique with a purposive sampling technique with a population of 100 respondents. With the criteria that UMKM have been operating for at least 3-2 years, transactions have used internet banking such as (Ovo, Go-Pay, Funds, Shopee-pay) in Pasuruan Regency. While the analysis technique used is multiple linear regression analysis with the calculation analysis tool using SPSS 24. The results of this study indicate that: 1. the financial knowledge variable has no positive and insignificant effect on MSME performance 2. The financial attitude variable has a positive and significant effect on MSME performance. 3. The financial behavior variable has no positive and significant effect on MSME performance. 4. The financial knowledge, financial attitude and financial behavior variables have a positive and significant effect on MSME performance.